Urinary tract infection and prolonged neonatal jaundice in term infants during the first two months of life: a descriptive study - Hameed, Numan N.; Ahmed, Nariman F.; Hassan, Qusay F. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Several causes stand behind prolonged neonatal Jaundice (Jaundice that persists more than 2 weeks). Objectives: To find out the frequency of association between Urinary tract infections (UTI) and prolonged neonatal jaundice in term infants during the first two months of life. Patients and methods: We conducted an observational prospective study in children welfare teaching hospital, Medical City Complex, Baghdad. Fifty term infants, less than two months of age, with clinically evident jaundice that has persisted for more than 14 days of life were enrolled; UTI was confirmed by urine culture and sensitivity. Demographic features, historical characteristics, laboratory investigations, abdominal ultrasound findings recorded and analyzed for each patient. J Fac Med Baghdad 2014; Vol.56, No .2 Received Feb .2014 Accepted May. 2014 Results: UTI was confirmed by urinary culture in 6 infants (12%). E. coli was the most common isolated microorganism. UTI was more common in female patients during the first 2 months of life (66%). Irritability was the most common associated clinical feature (83%). Conjugated bilirubin was found to be the most raised fraction among jaundiced infants with UTI. Jaundice resolved gradually upon treating UTI with proper antibiotics. Conclusions: UTI was found in 12% of infants of less than two months of age with prolonged neonatal jaundice; urine culture should be considered as a part of the diagnostic evaluation for any infant with prolonged neonatal jaundice beyond 14 days of life with unexplained etiology.